Primary Percutaneous Intervention for ST-Elevation Myocardial Infarction Patients: A State of The Art - Budi Satrijo (Heart Science Journal, 2022)
Primary PCI is the preferred reperfusion strategy in patients with STEMI within 12 h of symptom onset. Angiographically successful PPCI was defined as less than 30% residual stenosis by visual assessment and grade 3 TIMI flow achievement. Radial access is preferred over femoral access. Drug eluting stent (DES) implantation is more superior than bare metal stent (BMS) implantation or balloon angioplasty. In STEMI patients with cardiogenic shock, non-infarct related artery PCI during the index procedure should be considered.